Perlindungan Konsumen di Kedah - Hamzah, Rosyidi; Hamzah, Hamzah; Choon, Low Kah; Hidayatullah, MT; Adinda, Fadhel Arjuna (Yayasan Riset dan Pengembangan Intelektual, 2024)
Humans in their lives need everything from other people. To eat humans buy food, to move from one place to another requires vehicles. To communicate with other people regardless of distance requires communication tools and almost all aspects of human life require products or services. To provide a sense of security and peace for humans in using products or services, rules must be made to protect humans as consumer beings. Humans as consumer beings have basic rights that must be fulfilled such as a sense of security and the existence of a path to sue for losses. To remind consumers of the rights of consumers in Kedah, which so far have been poorly understood by the people of Kedah, we are doing community service.